Transmural Placement of Endocardial Pacing Leads in Patients With Congenital Heart Disease - Sandrio, Stany; Purbojo, Ariawan; Toka, Okan; Dittrich, Sven; Cesnjevar, Robert; Rueffer, Andre (Annals of Thoracic Surgery, 2016)
This study evaluates the feasibility and outcomes of transmural placement of endocardial leads (TML) in patients with congenital heart disease.Between October 2009 and May 2015, 29 TML procedures were performed in 27 patients. Leads are grouped according to their pacing site: atrial (TML-A, n = 24) or ventricular (TML-V, n = 12). The TML-V includes transatrial and transventricular approaches. Clinical outcome, functional properties of TML, and Kaplan-Meier freedom from lead dysfunction were evaluated.Median age was 4 years (range, 29 days to 43 years). Median follow-up duration was 2 years (range, 1 day to 5.7 years). There was no early mortality. Three late deaths were observed (2 unrelated, 1 related to pacing). In group TML-A, no lead dysfunction was noted. In group TML-V, there were 3 lead dislodgements and 1 lead fracture. Kaplan-Meier freedom from lead dysfunction after 0.5, 1, and 5 years, respectively, was 100% in group TML-A and 82% ± 11%, 73% ± 13%, and 59% ± 17% in group TML-V (log rank p < 0.01). Mean acute (at implantation) and chronic (at last follow-up) sensing thresholds were 3.1 ± 2.3 mV and 3.5 ± 2.5 mV in group TML-A and 11.6 ± 4.9 mV and 7.5 ± 4.6 mV in group TML-V, respectively. Mean acute and chronic pacing thresholds at 0.5 ms were 1.1 ± 0.6 V and 0.6 ± 0.3 V in group TML-A and 1.0 ± 0.6 V and 0.9 ± 0.5 V in group TML-V, respectively.The transmural approach provides an alternative method in patients with congenital cardiac defects who cannot receive transvenous leads and who have extensive epicardial scarring. Subanalysis shows superior midterm performance for TML-A compared with TML-V.
EVALuna2:25118